Effet des couverts arboré et arbustif sur les potentialités herbagères en forêt de chêne liège de la Mamora occidentale (Maroc) - Qarro M. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
Cork oak trees with their persistent leaves can be a limiting factor for herbaceous development and forage production. More than 80 per cent of tree cover limits herbaceous growth even grass species. Shrub cover enhances more grasses than leguminous development. The profitable influence of Teline linifilia shrub on herbaceous development is due to: soil enrichment by nitrogen, soil protection, reduction of water deficit, protection of desirable species against animal overgrazing. The optimal combination between tree and shrub covers for a good herbaceous potential is obtained with, respectively, 70 per cent and 60 per cent canopy cover.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)